Efficacy evaluation of ethanolic extract of Tamarindus indica L. leaves as possible alternate therapy in septic arthritis model of rabbit - Bishnu Prasad Sinha; Souvick Chatterjee; Rinku Buragohain; Indranil Samanta; Siddhartha Narayan Joardar; Prasenjit Mukherjee; Asit Kumar Maji; Partha Das; Tapan Kumar Mandal; Tapas Kumar Sar (BMC, 2019)
Abstract Background Our previous study exhibited free radicals scavenging and antioxidant activities of ethanolic and aqueous extracts of Tamarindus indica L. leaves in chronic sodium fluoride poisoning in rats. Tamarindus indica L. seed extract was also reported to have anti-arthritic efficacy by inhibiting cartilage and bone degrading factors. Therefore, an attempt was made to evaluate the effects of ethanolic extract of Tamarindus indica L. leaves in septic arthritis. Methods The safety study was performed by oral dosing of ethanolic extract of the plant leaves at 2 g kg− 1 for consecutive 28 days in rabbits. Septic arthritis was induced in rabbits by single intra-articular inoculation of 104 c.f.u. of Staphylococcus aureus to the left stifle joint and was monitored by bacterial colony count, some relevant biochemical parameters and histopathological interpretation of the affected joint. For efficacy evaluation in septic arthritis, linezolid at 75 mg kg− 1 twice daily for 10 days and the ethanolic extract of Tamarindus indica L. at 500 and 1000 mg kg− 1 for consecutive 14 days were administered orally to the rabbits after 48 h of induction of arthritis. Results In sub-acute toxicity study of Tamarindus indica L. leaves ethanolic extract, no significant change between days was found for aspertate aminotransferase, alanine transaminase, alkaline phosphatase, blood urea nitrogen and creatinine compared to day 0 values of the same group. The bacterial colony count of synovial fluid following Staphylococcus aureus inoculation to left stifle joint was found to be 1.08 ± 0.47 and 1.19 ± 0.29 c.f.u. mL− 1 in ethanolic extract low dose and high dose groups respectively, on day 2 which was reduced to 0.057 ± 0.036 c.f.u. mL− 1 and nil on day 16. The test extract was also found to markedly reduce simultaneous glucose difference, total protein ratio of serum and synovial fluid, joint radius and joint narrowing. Conclusion Ethanolic extract of Tamarindus indica L. leaves at 500 mg kg− 1 and 1000 mg kg− 1 produced anti-arthritic effects against S. aureus induced septic arthritis in rabbits. However, the ethanolic extract at 1000 mg kg− 1 orally for consecutive 14 days showed better effects in septic arthritis.